PENGARUH PEMBELAJARAN KOLABORATIF KONTEKSTUAL TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Ela Ulfiana; Rini Asnawati (Jurnal Pembelajaran Matematika, 2018)
Abstract:The quasi-experimental study aims to determine the effect of contextual collaborative learning on the improvement of students’ mathematics concept understanding. The population of this study is all students at the seventh grade of State Junior High School (SMPN) 1 Natar in the academic year of 2015/2016, which is distributed into thirteen classes. Sampling of this study uses purposive sampling technique, and the selected class is VII-B and VII-D as a sample. The design of this study is pretest-posttest control group design. The research data is obtained through pre-tests and post-tests in the form of essay. The result of hypothesis test shows that contextual collaborative learning influences the improvement of students’ mathematics concept understanding.Keywords:Collaborative Contextual, Conventional, Understanding of Mathematics Concepts.